2013
DOI: 10.21273/hortsci.48.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination of Arbutus unedo, A. andrachne and Their Natural Hybrid A. andrachnoides in Relation to Temperature and Period of Storage

Abstract: Arbutus unedo L., A. andrachne L., and their natural hybrid, A. ×andrachnoides Link, are the three Arbutus species of the Eastern Mediterranean Macchia. A. unedo is used as an ornamental plant and as cut foliage, whereas the other two species have the potential to be introduced to the floricultural industry. This study was carried out to clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…syriaca (Thanos and Doussi 1995), Coridothymus capitatus, Origanum vulgare subsp. hirtum, Satureja thymbra (Estrelles et al, 2010), whereas 15°C was found to be more effective for germination of the Mediterranean species Dianthus fruticosus (Papafotiou and Stragas, 2009), Globularia alypum (Bertsouklis and Papafotiou, 2010), and all the Arbutus species found in Greece (Bertsouklis and Papafotiou, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…syriaca (Thanos and Doussi 1995), Coridothymus capitatus, Origanum vulgare subsp. hirtum, Satureja thymbra (Estrelles et al, 2010), whereas 15°C was found to be more effective for germination of the Mediterranean species Dianthus fruticosus (Papafotiou and Stragas, 2009), Globularia alypum (Bertsouklis and Papafotiou, 2010), and all the Arbutus species found in Greece (Bertsouklis and Papafotiou, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…pomifera (Thanos and Doussi, 1995), and a number of other Mediterranean species, as Arbutus unedo, A. andrachne, A. × andrachnoides (Bertsouklis and Papafotiou, 2013), Dianthus fruticosus (Papafotiou and Stragas, 2009), Sideritis athoa (Papafotiou and Kalantzis, 2009a), Lithodora zahnii (Papafotiou and Kalantzis, 2009b). (Thanos and Doussi, 1995;Kadis and Georghiou, 2010;Vlachou et al, 2019), and for the Mediterranean species of Fabaceae Anthyllis barba-jovis (Morbidoni et al, 2008;Trigka and Papafotiou, 2017).…”
Section: Germinationmentioning
confidence: 99%
“…(Flora Europaea, 1996) are native in the eastern Mediterranean region including Greece. All three of these species are very attractive for ornamental use (Cervelli et al, 2012;Bertsouklis and Papafotiou, 2013) and of high value in forestry for reforestations because of their ability for resprouting from the lignotuber after a fire (Konstantinidis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%